Integrated Management Practices for Clubroot Disease (Plasmodiophora Brassicae Wor.) of Cauliflower in Palung, Makwanpur, Nepal - Adhikari, P; Khatiwada, A; Paneru, N; Tandan, P (SAARC Journal of Agriculture, 2020)
Club root is one of the most important diseases in the eastern hills of Nepal affecting the rural income as well as quantity and quality of Cauliflower production. A field experiment was conducted in Randomized Complete Block Design (RCBD) with 5 treatments and 4 replications during February to May, 2019. The experiment was conducted in the Farmer’s field in the disease prone area of Thaha municipality-4, Palung of Makwanpur district to assess the efficacy of five different treatments; Nebijin, Hatake, Trichoderma viride, Lime and control for the management or suppressing the club root disease. The effectiveness of the treatments against club root disease was evaluated along with their influence on growth parameters and yield parameters of white top variety of cauliflower. Different parameters such as disease incidence, percent disease index (PDI) or disease severity index (DSI) and percent disease control (PDI) were recorded using disease scoring scale. The treatments showed significant effect on the yield and disease parameters, but not on the vegetative parameters of cauliflower. The lowest disease incidence (50.2%) and severity index (26.8%) and the highest percent disease control (57.6%) was recorded in Nebijin. Moreover, the Marketable yield (Mtha-1) per plot was observed highest from Nebijin (48.27Mtha-1) and Trichoderma viride (47.39 Mtha-1) treatment. From the study it may concluded that the application of Nebijin was more effective for the management of clubroot disease of Cauliflower and the use of Hatake and Trichoderma virideas bio-fungicides were also giving the potential assuring measure for the controlling disease of Cauliflower. SAARC J. Agri., 18(1): 87-98 (2020)